Moluccas Local Wisdom in the Role of Marriage Arbitrator for Preventing Domestic Violence - Ahmad Lonthor; La Jamaa (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2020)
This research aims to reveal the Moluccas local wisdom through the existence of marriage arbitrators among Muslim community in Salahutu, Leihitu, and West Leihitu, Central Maluku. The data were collected through observation and interviews with community leaders, marriage arbitrators and their married sisters and then analyzed descriptively and qualitatively. The research results showed that the marriage arbitrators come from a male distant relative who was appointed by custom as a part of the marriage custom. The appointment aims to strengthen the family relationship between the bride (married sister) and the arbitrator in which they can help each other. Traditionally, an arbitrator serves to help the bride in both material and non-material aspects, particularly in preventing domestic violence. He can become a mediator, peacemaker, and helper of the economic hardship as well as preventing the married sister from psychological domestic violence. Furthermore, he can also provide protection for his married sister from the threat of her husband’s physical violence. This research found that the role of marriage arbitrators as peacemakers in preventing husband’s violence against their married sisters is relevant to hakamain concept in Islamic law as well as the provisions of